2022
DOI: 10.1107/s1600577522007949
|View full text |Cite
|
Sign up to set email alerts
|

Observation of water droplets in microporous layers for polymer electrolyte fuel cells by X-ray computed nano-tomography

Abstract: An X-ray computed nano-tomography (nano-CT) system has been established at the BL33XU beamline of SPring-8. The optical system consists of pseudo-Köhler illumination with a sector condenser zone plate, an apodization Fresnel zone plate as the objective lens, and a Zernike phase plate. The imaging detector is a fiber-coupling type X-ray camera. The performance of the X-ray nano-CT system was confirmed by imaging an X-ray test chart. The system was subsequently applied to the observation of a microporous layer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, this approach only provides information about the surface hydrophobicity, including the roughness factor. Other laboratory techniques, such as the Washburn and Wilhelmy methods, can be applied to measure the internal GDL wettability. Moreover, cyclic voltammetry (CV) measurements facilitate the assessment of internal GDL wettability based on the surface area of the wet GDL, as determined through the formation of an electrical double layer at the GDL/electrolyte interface. Advanced imaging techniques, including computed tomography (CT) , and radiography , using X-ray and neutron sources, are advantageous for elucidating the internal contact angle and water saturation level, respectively, in wet GDLs within PEFCs. Herein, we present a comprehensive analysis encompassing the pore size distribution, porosity, external and internal wettabilities, water saturation, and flooding tolerance of carbon papers with various PTFE contents to provide insights into the effective design of waterproofed carbon papers as cathode GDLs in PEFCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach only provides information about the surface hydrophobicity, including the roughness factor. Other laboratory techniques, such as the Washburn and Wilhelmy methods, can be applied to measure the internal GDL wettability. Moreover, cyclic voltammetry (CV) measurements facilitate the assessment of internal GDL wettability based on the surface area of the wet GDL, as determined through the formation of an electrical double layer at the GDL/electrolyte interface. Advanced imaging techniques, including computed tomography (CT) , and radiography , using X-ray and neutron sources, are advantageous for elucidating the internal contact angle and water saturation level, respectively, in wet GDLs within PEFCs. Herein, we present a comprehensive analysis encompassing the pore size distribution, porosity, external and internal wettabilities, water saturation, and flooding tolerance of carbon papers with various PTFE contents to provide insights into the effective design of waterproofed carbon papers as cathode GDLs in PEFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology and methodology have made it accessible to obtain high-resolution three-dimensional (3D) images of GDL structures. Many studies have been reported on extracting porosity and tortuosity as GDL structural parameters to understand the transport limitations in a dry GDL. ,, Recently, 3D images of nanoscale particles and pores within an MPL have been taken using focused ion beam scanning electron microscopy (FIB-SEM) , and synchrotron X-ray computed tomography (XCT). ,, The captured high-resolution 3D images provide the porosity of GDLs but not the “real” tortuosity toward the effective oxygen diffusion path. Therefore, tortuosity is often approximated as a function of porosity: ε/τ = ε γ , where γ is the empirical parameter depending on the structure. , …”
Section: Introductionmentioning
confidence: 99%
“…6,8,11−16 Recently, 3D images of nanoscale particles and pores within an MPL have been taken using focused ion beam scanning electron microscopy (FIB-SEM) 11, 12 and synchrotron X-ray computed tomography (XCT). 11,14−, 16 The captured high-resolution 3D images provide the porosity of GDLs but not the "real" tortuosity toward the effective oxygen diffusion path. Therefore, tortuosity is often approximated as a function of porosity: ε/τ = ε γ , where γ is the empirical parameter depending on the structure.…”
Section: Introductionmentioning
confidence: 99%